DAMPAK SUHU PIROLISIS TERHADAP KARBON AKTIF DARI BUNGA PINUS UNTUK MATERIAL PENDUKUNG KATALIS FUEL CELL - Pebi Riyanto; Trisma Jaya Saputra; Rany Puspita Dewi; Sigit Mujiarto; Raka Mahendra Sulistiyo (Scientific Journal of Mechanical Engineering Kinematika, 2026)
The high cost and limited durability of platinum-based catalysts remain major challenges for the large-scale commercialization of fuel cell. Therefore, alternative and more affordable catalyst support materials are needed. Biomass derived activated carbon offers a promising solution due to its porous structure, good electrical conductivity, and abundant raw material availability. This study aims to investigate the potential of Pinus merkusii pine cones as a precursor for activated carbon through pyrolysis and chemical activation using potassium hydroxide (KOH), as well as to evaluate its suitability as a fuel cell catalyst support material. Pyrolysis was conducted at temperatures of 400ºC, 600ºC, and 800ºC under a nitrogen inert atmosphere, followed by chemical activation. The resulting activated carbon was characterized using proximate analysis and Brunauer-Emmett-Teller (BET) analysis. The results indicate that increasing the pyrolysis temperature led to a reduction in biochar yield, moisture content, ash content, and volatile matter, while consistently enhancing the fixed carbon content and specific surface area. The optimal condition was achieved at a pyrolysis temperature of 800ºC, producing activated carbon with the highest fixed carbon content of 81.87%, a specific surface area of 42.83 m2/g, and a mesoporous structure with an average pore diameter of 3.23 nm. Nevertheless, the obtained specific surface area remains below the ideal value (>100 m²/g) for application as a fuel cell catalyst support, indicating that the synthesized material still requires further optimization in both the process and activation conditions.